Highly antimicrobial-resistant Nontyphoidal Salmonella from retail meats and clinical impact in children, Taiwan - Yi-Jung Chang; Mi-Chi Chen; Ye Feng; Lin-Hui Su; Hsin-Chieh Li; Hsin-Ping Yang; Min-Jia Yu; Chyi-Liang Chen; Cheng-Hsun Chiu (Elsevier, 2020)
Background: The epidemiology of nontyphoidal Salmonella (NTS) resistant to ciprofloxacin or ceftriaxone and its impact on patients' clinical course are rarely reported. Methods: Children with culture-proven salmonellosis treated in a medical center in northern Taiwan in 2017 were enrolled. To trace the source of Salmonella, Salmonella isolated from food samples were collected from markets. Antimicrobial susceptibility and serotypes were determined. Results: Among the 453 isolates, 122 (26.9%) were highly antimicrobial-resistant, as defined by resistance to ciprofloxacin or ceftriaxone or both. The most prevalent highly resistant serotype was S. Anatum (66, 54.1%). Salmonella was detected in 94.1%, 66.7%, and 8.6% of examined pork, chicken, and vegetables examined, respectively. S. Anatum (6, 21.4%) and S. Derby (6, 21.4%) were the major serotypes isolated. Majority of the S. Anatum (5, 83.3%) were highly antimicrobial-resistant. More patients infected by highly resistant Salmonella required carbapenem treatment (OR = 23.5, 95% confidence interval [CI] 2.8-192.7, P < 0.001). Patients with ceftriaxone-resistant NTS infections had a significantly longer hospital stay than others (P < 0.001). Totally, 34 (7.5%) presented with invasive diseases (31 bacteremia, 1 intestinal perforation, 1 toxic megacolon and 1 septic arthritis). Risk factors for invasive disease included prolonged fever for ≧5 days and infection occurring in warmer season from May to October. The rise of ambient temperature in northern Taiwan was associated with increasing Salmonella infections. Conclusions: Retail meats were the main source of highly antimicrobial-resistant NTS in northern Taiwan. Highly antimicrobial resistance significantly impacted the clinical course and treatment of children with NTS infection.